Obstetric bleeding among women with inherited bleeding disorders: a retrospective study. (5th October 2016) - Hawke, L.; Grabell, J.; Sim, W.; Thibeault, L.; Muir, E.; Hopman, W.; Smith, G.; James, P.
Abstract : Introduction: Women with inherited bleeding disorders are at increased risk for bleeding complications during pregnancy and the postpartum period, particularly postpartum haemorrhage (PPH). Aim: This retrospective study evaluates pregnancy management through the Inherited Bleeding Disorders Clinic of Southeastern Ontario, the clinical factors associated with pregnancy‐related abnormal bleeding and assesses tranexamic acid use in the postpartum treatment of bleeding disorder patients. Methods: A chart review of 62 pregnancies, from 33 women, evaluated patient characteristics (age, haemostatic factor levels) and delivery conditions (mode of delivery, postpartum treatment) in relation to abnormal postpartum bleeding. Results: This cohort revealed increased risk of immediate PPH with increased age at delivery (mean age: 30.1 years with PPH, 26.5 years without PPH, P < 0.013), and birth by vaginal delivery ( P < 0.042). Low von Willebrand factor (VWF) antigen or factor VIII (FVIII) in the third trimester was not associated with an increased risk of PPH; however, low VWF:RCo was associated with increased immediate PPH despite treatment with continuous factor infusion ( P < 0.042). Women treated with tranexamic acid postpartum had less severe bleeding in the 6‐week postpartum ( P < 0.049) with no thrombotic complications. Conclusions: This study contributes to the growing body of work aimed at optimizing management of bleeding disorder patients through pregnancy and the postpartum period, showing patients are at a higher risk of PPH as they age. Risk factors such as low third trimester VWF:RCo have been identified. Treatment with tranexamic acid in the postpartum period is associated with a reduced incidence of abnormal postpartum bleeding.